Вивчення геномів рослин Deschampsia antarctica Desv. з різних локалітетів Прибережної Антарктики за допомогою хромосомних та молекулярних маркерів - Твардовська, М.О.; Андрєєв, І.О.; Амосова, А.В.; Спірідонова, К.В.; Навроцька, Д.О.; Саматадзе, Т.Е.; Зощук, С.А.; Муравенко, О.В.; Кунах, В.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. To perform molecular cytogenetic analysis of D. antarctica plants from different localities of maritime Antarctic. Methods. Cytogenetic analysis, С-banding, DAPI-banding, fluorescent in situ hybridization, silver-staining technique for nucleolar organizer regions, PCR-analysis. Results. Chromosome number 2n = 26 was determined in D. antarctica plants from two localities of Maritime Antarctic (Darboux and Galindez Islands). Karyotypes of plants from Darboux Island were found to contain 1 to 3 supernumerary chromosomes. FISH-analysis revealed 10 5S rDNA loci found on five A-chromosome pairs, as well as additional loci were localized on some of the B-chromosomes. Large 26S rDNA loci were located in the terminal positions on short arms of two submetacentric chromosome pairs. Genetic analysis of the plants was performed using polymorphic ISSR- and IRAP-markers. Jaccard genetic distance between the D. antarctica accessions under study was calculated from the data of PCR-analysis and compared to the data of assessment of D. antarctica genetic variability in the region. Conclusions. Using chromosomal and molecular markers in analysis of D. antarctica karyotype we succeded in revealing C-banding and DAPI-banding polymorphism. Furthermore, two transcriptionally active nucleolar organizer regions were identified. Molecular genetic analysis using polymorphic ISSR-markers demonstrated that genetic differences between the accessions under study fell in a range of within population variation that was found for the plants from investigated region.